An investigation into the cultural contents available in the reading passages of “English 12”, students’ attitudes and expectations toward the cultural contents to be loaded to this textbook and cultural learning at Phuc Tho High School - Vũ, Thị Tuyết (2020)
The main purposes of the this study are: (1) to examine the state of references to different cultural groups and cultural categories presented in the reading passages of the textbook English 12, (2) to find out the learners‟ attitudes and expectations on cultural contents in the textbook English 12 and their culture learning at Phuc Tho high school. (3) to give some pedagogical implications that may raise students‟ cultural awareness and hope to contribute some possitive changes in teaching and learning English in the current context at Phuc Tho High school. For the mentioned aims, a number of research questions as the objectives of the study will be raised for investigation: To what extent are the cultural groups represented in reading passages of English 12 textbook ? What categories reflecting cultural content does English 12 textbook introduce in reading passages and to what extent? What are the attitudes and expectations of grade-12 students Phuc Tho high school towards cultural contents in English 12 textbook? What are the attitudes and expectations of grade-12 students towards cultural learning at Phuc Tho high school ?